Hierarchical Supramolecular Self‐Assembly: Fabrication and Visualization of Multiblock Microstructures. (2nd November 2022) - Shi, Xiujuan; Zhang, Jun; Liu, Junkai; Zhao, Xueqian; Wang, Haoran; Wei, Peifa; Zhang, Xiaodong; Ni, Xin‐Long; Sung, Herman H.‐Y.; Williams, Ian D.; Ng, Wai Kit; Wong, Kam Sing; et al.
Abstract: Due to the fast dynamics and re‐equilibration of supramolecular self‐assembly, bottom‐up molecular strategies to fabricate well‐defined and controllable multiblock structures are rare. Herein, we propose a new concept for fabrication of fluorescent multiblock microcolumns containing 1 to 7 blocks via hierarchical supramolecular self‐assembly based on cucurbit[8]uril (CB[8]), NaBr and an AIEgen guest. Through the complexation between CB[8] and different numbers of AIEgen guests (2, 1, 0), the competitive displacement caused by the binding of the sodium cation to the CB[8] portal, and the reversible assembly of positively charged guests in salt solutions, one‐pot hierarchical supramolecular self‐assembly is realized. The molecular structure of each block is analyzed by single‐crystal X‐ray diffraction. The AIEgen enables the self‐assembly of multiblocks to be visualized, understood, and regulated. Abstract : Fluorescent multiblock microcolumns are fabricated relying on the cooperation between the controllable host‐guest complexation of cucurbit[8]uril (CB[8]) and AIEgen guest and the hierarchical supramolecular self‐assembly based on CB[8], NaBr and AIEgen guest. The AIEgen enables the self‐assembly to be visualized, understood, and regulated.